Combinations of single-top-quark production cross-section measurements and |fLVVtb| determinations at sv = 7 and 8 TeV with the ATLAS and CMS experiments; Journal of High Energy Physics; Vol. 2019, iss. 5 - Aaboud M.; Aad G. Georges; Abbott B. K. Brad; Abbott D. C.; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen